On the Linear Complexity of Generalized Cyclotomic Sequences with Odd Period - V. A. Edemskiy (Учёные записки Казанского университета: Серия Физико-математические науки)
The linear complexity of new generalized cyclotomic sequences with odd period was estimated. The sequences were deﬁned using generalized cyclotomic classes composite modulo. Conditions suﬃcient for the existence of binary and non-binary sequences with high linear complexity were obtained. The earlier results on the linear complexity of sequences with the period equal to the power of a prime were generalized.